2013
DOI: 10.1016/s1734-1140(13)71474-9
|View full text |Cite
|
Sign up to set email alerts
|

Influence of chronic stress on brain corticosteroid receptors and HPA axis activity

Abstract: Comparison of the dynamics of changes in plasma ACTH and corticosterone level with respective alterations in GR and MR in brain structures suggests that the buffering effect of repeated stress depends on the period of habituation to stress and the brain structure involved in regulation of these stress response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
35
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(43 citation statements)
references
References 40 publications
7
35
1
Order By: Relevance
“…The HPA axis exhibits marked adaptation of responsiveness following exposure to a single stressor, which in turn can lead both to facilitation of the subsequent response and habituation after following exposures. Nevertheless, the habituation phenomenon is considered stressor specific, such that subsequent exposure to a heterotypic stressor restores or potentiates the release of glucocorticoids (12,15,18,39). In the present study, the plasma corticosterone levels were found significantly higher in AS and CHeS-loaded rats compared with the rats under NS and CHS conditions.…”
Section: Discussioncontrasting
confidence: 39%
See 1 more Smart Citation
“…The HPA axis exhibits marked adaptation of responsiveness following exposure to a single stressor, which in turn can lead both to facilitation of the subsequent response and habituation after following exposures. Nevertheless, the habituation phenomenon is considered stressor specific, such that subsequent exposure to a heterotypic stressor restores or potentiates the release of glucocorticoids (12,15,18,39). In the present study, the plasma corticosterone levels were found significantly higher in AS and CHeS-loaded rats compared with the rats under NS and CHS conditions.…”
Section: Discussioncontrasting
confidence: 39%
“…HPA function is regulated by negative feedback, whereby circulating glucocorticoids inhibit their own release by acting at pituitary and hypothalamic levels via the corticosteroid receptors. The neuroendocrine response to many stressors is reduced after repeated or chronic exposure (18,39). The HPA axis exhibits marked adaptation of responsiveness following exposure to a single stressor, which in turn can lead both to facilitation of the subsequent response and habituation after following exposures.…”
Section: Discussionmentioning
confidence: 99%
“…Seminal studies (Schulkin et al , 1994; McEwen & Sapolsky, 1995; Popoli et al , 2011) support this notion by documenting that corticosteroids released from the adrenals do not only produce feedback inhibition of hypothalamic and pituitary hormone secretion (Akana et al , 1992) but directly regulate limbic and reward circuits (Sapolsky, 2003) to gate coping and flexibility (e.g., “flight or fight” behaviors; Eriksen et al , 1999; McEwen et al , 2012), motivation (McEwen, 2005), memory (Roozendaal et al , 2009), and fear extinction (Korte, 2001; McEwen, 2005). The prefrontal cortex (PFC) has emerged as a central site to orchestrate coordinated responses to acute stress (McEwen, 2007) with glucocorticoid and mineralocorticoid receptors modulating its ability to integrate upstream emotional, sensory, cognitive, and spatial inputs (Patel et al , 2008; Gadek‐Michalska et al , 2013; Caudal et al , 2014). …”
Section: Introductionmentioning
confidence: 99%
“…Published evidence has shown that both acute and chronic restraint stress can induce increased adrenocorticotropic hormone and corticosterone levels in both plasma and prefrontal brain, accompanied by a reduction in the levels of glucocorticoid receptors in the prefrontal cortex [12,26]. However, since no major alterations were evident in animals subjected to acute stress, we hypothesize that these effects could constitute early triggering signals for the display of adaptive/compensatory responses to handle stressing conditions and recover the compromised homeostasis.…”
Section: Discussionmentioning
confidence: 81%